ANALYSIS OF THE RANGE OF MEDICINES USED TO TREAT COMMON OCCUPATIONAL DISEASES OF COAL INDUSTRY WORKERS - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Ирина Герасимовна Танцерева; Вера Юрьевна Павлова (Медицина в Кузбассе)
The goal is to analyze the target segment of the pharmaceutical market of drugs for the treatment of common occupational diseases of coal industry workers and to identify the presence of various product items of the studied range, in order to assess the effectiveness of treatment and prevention.